Comparison of Fentanyl and Tramadol on Pain Sensitivity in Rat Model of Traumatic Barin Injury - Deswita, Rinda; Jasa, Zafrullah Khany; Rahmi, Rahmi (Journal of Anaesthesia and Pain, 2025)
Background: Traumatic Brain Injury (TBI) is intracranial tissue damage caused by mechanical processes originating from outside that cause structurally and functionally brain damage. After TBI, these animals often exhibit exaggerated responses to otherwise mild pain stimuli, a condition mimicking chronic pain observed in human TBI patients.Methods: This laboratory experimental study used a pretest-posttest control group design. A traumatic brain injury (TBI) rat model was created using the Feeney weight drop method. Rats received intravenous fentanyl or tramadol every 8 hours for three days. Pain thresholds were measured before and at 1, 6, 24, and 72 hours, and 7 days after TBI.Results: Pain sensitivity peaked at 6 and 24 hours post-trauma, with the control group showing a significant drop in Von Frey test scores. In contrast, the fentanyl and tramadol groups showed gradual improvement from 6 hours, with stable recovery by 72 hours. By day 7, both treatment groups returned to near-baseline sensitivity, while the control group remained impaired. Statistical analysis showed a significant difference between control and intervention groups (p < 0.05). Conclusion: Both fentanyl and tramadol improved pain sensitivity in the early phase after TBI and restored thresholds close to baseline state before TBI while the control group did not.